UJI KUALITAS SUMBER AIR PEGUNUNGAN MENGGUNAKAN METODE MOST PROBABLE NUMBER DI DESA TANJUNG TULUNGAGUNG - Rizqi Asri Fauzi Nugraha; Yunita Diyah Safitri; Novintan Elistya Diyah Purnamawati (Journal of Indonesian Medical Laboratory and Science, 2023)
Mountain springs is a source of clean water that is commonly used by rural communities to fulfil their daily water needs such as washing, bathing and cooking. The lack of clean water facilities in Indonesia is a problem that has not been resolved to date. The habits of the people in Tanjung Tulungagung Village is using mountain spring water for consumption as drinking water without boiling it first. Unboiled water has a tendency to be polluted by microbes, one of which is the coliform group. Coliform bacteria was known to cause several diseases, such as diarrhea, dysentery and cholera. The purpose of this study was to determine the quality of water by observing the growth of coliform bacteria in mountain water that consumed by residents in Tanjung Village, Sendang Tulungagung District. The method used in this study is the Most Probable Number (MPN). The results of this study showed that the number of Coliform contained in repeat samples 1, 2, 3 & 4 respectively, were 900, 1600, 1600, 1600 MPN/100 ml, then the data was compared with the SNI issued by the National Standardization Agency. Based on SNI 3719:2014, the requirements for the Most Likely Number (APM) for drinking water are not more than <2/100 ml. The conclusion from this study is that the water used by the people of Tanjung Village, Sendang District, Tulungagung Regency is not suitable for direct consumption without being processed first.